Acesso e repartição de benefícios dos recursos genéticos marinhos brasileiros: incompatibilidade entre o regime internacional e a nova lei da biodiversidade? - Girão, Edwiges Coelho (2017)
The Biodiversity Law (Law No. 13.123, of May 20, 2015) establishes new rules on access to and sharing of benefits arising from the utilization of genetic brazilian resources. The new rules apply to marine genetic resources found in situ on the territorial sea and the exclusive economic zone, marine areas in which Brazil holds the management of living resources, in accordance with the United Nations Convention on the Law Sea. The Biodiversity Law brings significant innovations to be examined in comparison with the Convention on Biological Diversity and the Nagoya Protocol, international standards that recognize the sovereignty of states over their natural resources. The present study intends to investigate if there is incompatibility between the new rules created by Law 13.123/2015 and the international regime, regarding adequate access to marine genetic resources and the fair and equitable sharing of its benefits. In the perspective of the international regime of access and benefit sharing of marine resources, inadequacy between the new law and international standards may lead to inaccuracies in the control of access to marine resources and in the absence of a fair and equitable sharing of the benefits of marine biodiversity. In the perspective of the international regime of access and benefit sharing of marine resources, inadequacy between the new law and international standards may lead to inaccuracies in the control of access to marine resources and in the absence of a fair and equitable sharing of the benefits of marine biodiversity. Indeed, adequate access to marine biodiversity should be based on prior informed consent covering the need for greater control by the coastal State in the face of the impacts of bioprospecting on the marine environment. Also, the fair and equitable sharing of marine resources should involve biotechnological transfer to the supplier states. It is concluded that the new law departs from these guidelines by oversimplifying the access procedure and by greatly favoring the sharing of benefits in the monetary form. The methodology is qualitative research literature.